ALLELOPATHIC POTENTIAL AND PHYTOCHEMICAL SCREENING OF FOUR MEDICINAL PLANTS OF NEPAL - Sharma, Swasti; Devkota, Ajana (Scientific World, 2015)
The laboratory tests were conducted to evaluate the allelopathic potential and phytochemical study of the four selected medicinal plants Ageratum conyzoides, Eclipta prostrata, Cannabis sativa and Woodfordia fructicosa. The aqueous extract bioassay of the plants with stem and root were conducted on the two test seeds Triticum aestivum (wheat) and Pisum sativum (pea) by filter paper method. Germination, seedling growth and biomass production were observed under the allelopathic study whereas under phytochemical study qualitative or presence or absence and quantitative or crude amount of the phytochemicals present were also estimated. For the allelopathic studies the germination and seedling growth of wheat and pea test species under the different concentrations 2 %, 4%, 6%, 8% and 10% of the stem and root extracts of the plants under study were carried out. Increased concentration of the aqueous extracts of the plants increased the inhibitory rate or decreased the germination and seedling growth.Species sensitivity varied with the test seeds and alkaloid, flavonoid, saponin, tannin, phenol, glycoside and essential oil were the phytochemicals present in the plant extracts. Scientific World, Vol. 12, No. 12, September 2014, page 56-61